UJI BAKTERIOLOGIS KUNYIT GILING (Curcuma domestica Val.) DARI BEBERAPA PASAR TRADISIONAL DI KOTA PADANG - Sepriani, Yuni; Fifendy, Mades; Periadnadi, Periadnadi (STKIP PGRI Sumbar, 2013)
AbstrakTurmeric (Curcuma domestica Val.) Is a plant with a rhizome that many are, both in the scale of household or industrial scale. Concomitant development of technology, the production of ready-made mealsfavored by society, one of which is tumeric. This research was carried out with the aim to do bacteriologicaltesting of tumeric (Curcuma domestica Val.) Of some traditional market in Padang, implemented in June2013 at the Laboratory of Microbiology Department of Biology, University of Andalas Padang. The research was conducted with descriptive methods, purposive sampling is done at 5 sampling traditional marketsnamely Padang city, Bandar Buat market, Gaung market, Lubuk Buaya market, Simpang Haru market, andSiteba market. Further bacteriological testing done with these steps: 1. Test estimation (Presumtive test), 2. test assertions (Confirmed test) and 3. completion test (Completed test) using the MPN method (MostProbable Number) by using a combination of 5:1:1. Results obtained from this study tumeric samples containing bacteria with a total range of 23 x 105Â cells / ml - 155 x 105Â cells / ml. Highest total bacteria recovered in tumeric sold at Gaung market in sample 1 while the lowest total bacteria recovered in tumeric Siteba sold in markets in the sample 1. Tumeric samples from five traditional market in Padang city has coliform bacteria MPN value range from 2.0 to 240.0 ml sel/100 and bacteria E. coli from 4.0 to 240.0 ml sel/100. This proves that tumeric being sold from a number of traditional markets in the city of Padanggenerally not eligible consumed because they contain bacteria E. coli > 3 colonies / g and coliform bacteria >100 colonies / g.Â